THE EFFECT OF ENVIRONMENTAL ACCOUNTING, OPERATING CASH FLOW, AND FIRM SIZE ON FIRM VALUE - Ni Nyoman Aria Niska PUTRI; I Gusti Ayu Made Asri Dwija PUTRI (CV. Adiba Aisha Amira, 2025)
Firm value represents the fair market valuation of a business entity, reflecting the perceptions or assessments of its success—typically indicated by stock price performance. This study aims to provide empirical evidence on the influence of environmental accounting, operating cash flow, and firm size on firm value. A quantitative research approach was employed in this study. The research population comprises all companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period, with a purposive sampling technique yielding a total of 2,061 firm-year observations. Data analysis was conducted using multiple linear regression with the aid of STATA 17 software. The findings indicate that environmental accounting has a significant positive effect on firm value. In contrast, operating cash flow does not exhibit a statistically significant impact. Interestingly, firm size demonstrates a negative effect on firm value. These results contribute to the ongoing discourse in signal theory and stakeholder theory, offering deeper insights into how environmental practices and company characteristics influence market perceptions. Furthermore, the findings provide practical implications for investors and corporate management in strategic decision-making processes. They also serve as a valuable reference for future researchers seeking to explore related variables within the context of firm valuation.